Effect of smoking reduction and cessation on the plasma levels of the oxidative stress biomarker glutathione – Post-hoc analysis of data from a smoking cessation trial - Mons, Ute; Muscat, Joshua E.; Modesto, Jennifer; Richie, John P.; Brenner, Hermann (Free radical biology & medicine, 2016)
Cigarette smoke contains high concentrations of free radical components that induce oxidative stress. Smoking-induced oxidative stress is thought to contribute to chronic obstructive pulmonary disease, cardiovascular disease and lung cancer through degenerative processes in the lung and other tissues. It is uncertain however whether smoking cessation lowers the burden of oxidative stress. We used data from a randomized controlled cessation trial of 434 current smokers for a post-hoc examination of the effects of smoking cessation on blood plasma levels of total glutathione (tGSH), the most abundant endogenous antioxidant in cells, and total cysteine (tCys), an amino acid and constituent of glutathione. Smoking status was validated based on serum cotinine levels. Multivariate linear mixed models were fitted to examine the association of smoking cessation and change in cigarette consumption with tGSH and tCys. After 12 months follow-up, quitters (n=55) had significantly increased levels of tGSH compared to subjects who continued to smoke (P<0.01). No significant change in tGSH was found for subjects who continued to smoke but reduced their intensity of smoking. No significant effect of smoking cessation or reduction was observed on levels of tCys. These results suggest that smoking cessation but not smoking reduction reduces levels of oxidative stress. •We exploit data from a randomized controlled cessation trial of 434 current smokers.•We examine effects of smoking cessation on plasma levels of tGSH and tCys.•tGSH-levels significantly increased after cessation, but not after smoking reduction.•No significant effect of smoking cessation was observed on levels of tCys.•Results suggest that smoking cessation but not reduction reduces levels of oxidative stress.